Life cycle evaluation of hydrogen and other potential fuels for aircrafts - Bicer, Yusuf; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
In the present study, hydrogen and some other alternative fuels (such as ammonia, methanol, ethanol, liquefied natural gas) are considered for aviation applications under a comprehensive life cycle assessment study and are evaluated comparatively with the conventional kerosene based jet fuel for various impact categories. Therefore, this study is performed with a well-to-wake approach to evaluate the overall life cycle of an aircraft running on these conventional and alternative fuels. Both conventional and renewable fuel routes are considered for the production of ammonia and hydrogen fuels. Although there are modifications required to fulfill the aviation fuel specifications for such alternative fuels, the long term viability and environmental sustainability make them attractive solutions for the future of aviation industry. This study uses a life cycle assessment of an average aircraft utilizing various alternative aviation fuels to determine the relative environmental impact of each life cycle phase. The life cycle phases included in the analyses are as follows: (i) production, operation and maintenance of the aircraft, (ii) construction, maintenance and disposal of the airport, (iii) production, transportation and utilization of the aviation fuel in the aircraft. The results show that hydrogen and liquefied natural gas represent more environmentally benign alternatives although fuel costs are higher compared to ammonia, jet fuel and methanol. The total GHG emissions from hydropower based ammonia and hydrogen are calculated to be about 0.24 kg CO2 eq. per traveled tonne-km and 0.03 kg CO2 eq. per traveled tonne-km, respectively. Renewable based ammonia and hydrogen fueled aircrafts can further decrease the overall environmental impact in many categories allowing a brighter future for aviation industry. 2016 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydrogen economy; Fuels; Aircrafts; Aviation; Life cycle assessment; Environmental impact; LIQUID-HYDROGEN; EMISSIONS; KEROSENE; FUTURE; Chemistry; Electrochemistry; Energy & Fuels